Laying Waste to Mercury: Inexpensive Sorbents Made from Sulfur and Recycled Cooking Oils. Issue 64 (30th August 2017) - Worthington, Max J. H.; Kucera, Renata L.; Albuquerque, Inês S.; Gibson, Christopher T.; Sibley, Alexander; Slattery, Ashley D.; Campbell, Jonathan A.; Alboaiji, Salah F. K.; Muller, Katherine A.; Young, Jason; Adamson, Nick; Gascooke, Jason R.; et al.
Abstract: Mercury pollution threatens the environment and human health across the globe. This neurotoxic substance is encountered in artisanal gold mining, coal combustion, oil and gas refining, waste incineration, chloralkali plant operation, metallurgy, and areas of agriculture in which mercury‐rich fungicides are used. Thousands of tonnes of mercury are emitted annually through these activities. With the Minamata Convention on Mercury entering force this year, increasing regulation of mercury pollution is imminent. It is therefore critical to provide inexpensive and scalable mercury sorbents. The research herein addresses this need by introducing low‐cost mercury sorbents made solely from sulfur and unsaturated cooking oils. A porous version of the polymer was prepared by simply synthesising the polymer in the presence of a sodium chloride porogen. The resulting material is a rubber that captures liquid mercury metal, mercury vapour, inorganic mercury bound to organic matter, and highly toxic alkylmercury compounds. Mercury removal from air, water and soil was demonstrated. Because sulfur is a by‐product of petroleum refining and spent cooking oils from the food industry are suitable starting materials, these mercury‐capturing polymers can be synthesised entirely from waste and supplied on multi‐kilogram scales. This study is therefore an advance in waste valorisation and environmental chemistry. Abstract : Laying waste to mercury pollution : A sustainable rubber made from sulfur and recycled cooking oil is a general sorbent for diverse forms of mercury pollution.